The Rebuilding of a Life after Jail Time for Fraud - Joseph Lam; Kieran James; Jenny Kwai-Sim Leung (Australasian Accounting, Business and Finance Journal, 2012)
After a brief introduction from the second-mentioned author, which sets the scene for the story as Cabramatta and environs in Sydney’s outer south-western suburbs, the first-mentioned author takes over and gives readers his life story beginning with his family fleeing the Communists in South Vietnam, moving on to his days in his twenties running his own accounting firm in western Sydney to tax frauds, court case, and jail time. He moves on to explain how he began a conscious strategy to re-create his life existentially by studying MBA in prison. The first-mentioned author concludes with an important personal message, borne out of his own personal life experiences, to readers of the journal followed by some reflection from the second-mentioned author. This article will be of interest to accounting students, accounting educators, and any young (or not so young) accounting professionals under temptation to commit fraud to make a quick dollar. Sartrean existentialism and Marxist-Stalinist ethics inform the analysis of the case by the second-mentioned author. The role of gambling addiction in the story is topical given Singapore’s recent decision to open two new casinos, the first to open in the city-state since its 1965 independence.
Keywords: Accounting education; Business ethics; existentialism; gambling addiction; Sydney; tax fraud; Vietnamese-Australians; Vietnamese diaspora